2022
DOI: 10.3389/fphar.2022.1091779
|View full text |Cite
|
Sign up to set email alerts
|

The significance of glycolysis in tumor progression and its relationship with the tumor microenvironment

Abstract: It is well known that tumor cells rely mainly on aerobic glycolysis for energy production even in the presence of oxygen, and glycolysis is a known modulator of tumorigenesis and tumor development. The tumor microenvironment (TME) is composed of tumor cells, various immune cells, cytokines, and extracellular matrix, among other factors, and is a complex niche supporting the survival and development of tumor cells and through which they interact and co-evolve with other tumor cells. In recent years, there has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 99 publications
0
21
0
Order By: Relevance
“…An acidic environment is frequently observed in tumors due to the lack of oxygen ( 40 ). In addition, lactic acid, a metabolite of glycolysis, can also accumulate in the TME, leading to reduced extracellular pH ( 41 ). In these conditions, VISTA can potentially interact with specific ligands like PSGL-1.…”
Section: Discussionmentioning
confidence: 99%
“…An acidic environment is frequently observed in tumors due to the lack of oxygen ( 40 ). In addition, lactic acid, a metabolite of glycolysis, can also accumulate in the TME, leading to reduced extracellular pH ( 41 ). In these conditions, VISTA can potentially interact with specific ligands like PSGL-1.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that this requirement is significantly enhanced upon induction of mutant GNAS on a mutant Ras background. Increased glycolysis is generally related with tumor progression and aggressiveness via increased substrate production [32]. Lactate, which is the final product of glycolysis, can acidify the tumor microenvironment [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Increased glycolysis is generally related with tumor progression and aggressiveness via increased substrate production [32]. Lactate, which is the final product of glycolysis, can acidify the tumor microenvironment [32, 33]. Tumor microenvironment acidification promotes proliferation, resistance to apoptosis, invasiveness, metastatic potential, and aggressiveness of tumor cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…The gene SLC7A5 promotes proliferation, migration, and invasion in gastric cancer [31], colorectal cancer [32], endometrial cancer [33], and breast cancer [34]. Furthermore, a pan-cancer survival analysis of SLC7A5, including 33 tumors in the GEPIA2 public database, also showed that high SLC7A5 expression signi cantly reduces survivals (Figure 5A).…”
Section: Mф-glioma Fusion Hybrids Exhibit Elevated Expression Of Mф-d...mentioning
confidence: 91%